Association of TNFRSF12A Methylation With Prognosis in Hepatocellular Carcinoma With History of Alcohol Consumption - Wang, Yi; Zhang, Sina; Xie, Xiaozai; Chen, Ziyan; Wu, Lijun; Yu, Zhengping; Guo, Xiaojuan; Chen, Gang (Frontiers in Genetics, 2020)
Background: Hepatocellular carcinoma (HCC) is the third most common cause of mortality worldwide with a poor prognosis. Alcoholic liver disease accounts for approximately one-third of all HCC cases. TNFRSF12A hepatic expression correlates with disease severity. Overexpression of TNFRSF12A in HCC might be an indicator of more aggressive tumours and worse clinical outcomes. Epigenetic mechanisms including hypomethylation induced activation of silent oncogenes, loss of imprint, genomic instability of repetitive DNA sequence activation and translocation, may contribute to HCC. Objectives: This study aims to determine the methylation level of TNFRSF12A in HCC patients with a history of alcohol consumption. The changes in methylation levels of TNFRSF12A may be regulated by the action of methyltransferases, thus affecting the prognosis of HCC cases, especially those with alcohol consumption history. Method: We mined open source database (TCGA and GEO database) to explain the significance of methylated sites in TNFRSF12A in liver disease, their association with prognosis, identified relevant methylation sites. Further analysis was performed to identify correlations between TNFRSF12A, methylation sites and DNA methylase in HCC with alcohol and non-alcohol consumption. Results: The first time discovered that the methylation levels of two methylation sites of cg00510447 and cg26808293 could identify hepatocellular carcinoma and other liver diseases. We also found that hypomethylation of these sites in cases of alcoholic cirrhosis were lower than those in other liver diseases of non-hepatocellular carcinoma. Also, the correlation and prognostic analysis of these two sites revealed hypomethylation combined with high expression of TNFRSF12A in patients with alcohol-depleted HCC linked with poor prognosis. The hypomethylation of the cg26808293 site in males HCC in the presence and absence of alcohol consumption indicated significantly poor prognosis. Analysis further revealed that DNMT3L may regulate TNFRSF12A methylation, thus affecting the prognosis of HCC patients with a history of alcohol consumption and the occurrence and development of the disease. Conclusions: The study identified novel epigenetic drivers and clinically useful methylation markers of HCC. It provided a new epigenetic concept for the mechanism of development of HCC. It also provides a new direction for whether the alcoholic liver disease can eventually evolve into HCC through epigenetic mechanisms.